2014
DOI: 10.1002/mas.21447
|View full text |Cite
|
Sign up to set email alerts
|

Global discovery of protein kinases and other nucleotide‐binding proteins by mass spectrometry

Abstract: Nucleotide-binding proteins, such as protein kinases, ATPases and GTP-binding proteins, are among the most important families of proteins that are involved in a number of pivotal cellular processes. However, global study of the structure, function, and expression level of nucleotide-binding proteins as well as protein–nucleotide interactions can hardly be achieved with the use of conventional approaches owing to enormous diversity of the nucleotide-binding protein family. Recent advances in mass spectrometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 119 publications
(199 reference statements)
0
27
0
2
Order By: Relevance
“…LC-MS/MS can additionally require relatively large amounts of starting sample material to identify and accurately quantify low abundant protein variants (e.g., specific sites of phosphorylation, acetylation, methylation, point mutations). Furthermore, sample preparation workflows can require multi-dimensional separation strategies and/or targeted depletions [18][19][20][21], while subsequent bioinformatic analysis can require deconstruction of chimeric spectra [22] to effectively quantify specific proteins of interest.…”
Section: Introductionmentioning
confidence: 99%
“…LC-MS/MS can additionally require relatively large amounts of starting sample material to identify and accurately quantify low abundant protein variants (e.g., specific sites of phosphorylation, acetylation, methylation, point mutations). Furthermore, sample preparation workflows can require multi-dimensional separation strategies and/or targeted depletions [18][19][20][21], while subsequent bioinformatic analysis can require deconstruction of chimeric spectra [22] to effectively quantify specific proteins of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of metabolic adaptation and reprogramming is highly pleiotropic, coordinating regulation of kinases, transcription factors, and other proteins across multiple signaling pathways (Brooks Robey et al , 2015). Kinases are key transducers of signaling pathways, often clinically actionable, and can be unbiasedly profiled by ABPP (Duncan et al , 2012; Xiao & Wang, 2016). Since GSEA indicated that MAPKs were uniquely upregulated in SKLMS1 cells upon arginine starvation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All these affinity matrices were based on the 3 most complementary probes (19,15 and 1) which, in combination as the first matrix, were predicted to enrich 315 kinases ( Figure 3B). One or two more good probes among probe 5, 7, 18 and 20b were added to this core matrix to generate seven other matrices.…”
Section: Kinome Purification Using Mixed Probe Matricesmentioning
confidence: 99%
“…The chemical proteomics concept intends to circumvent the choice of kinases to include in a panel and the limitations of the recombinant proteins assays by covering the native kinome in, ideally unbiased, pull-down experiments. [17][18][19] Examples for such ideas are drug-centric profiling, [20][21][22] the KiNativ technology and other covalent acyl nucleotide probes, 23,24 the Kinobeads technology 25,26 or other multiplexed kinase inhibitors beads. 27,28 Today, these experiments are typically analyzed using quantitative mass spectrometry as an assay readout.…”
Section: Introductionmentioning
confidence: 99%